2020
DOI: 10.3390/agriculture10080329
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus in Spring Barley and Italian Rye-Grass Biomass as an Effect of Inter-Species Interactions under Water Deficit

Abstract: With global warming, the problem of soil water deficit is growing in Central Europe, including Poland, and the use of catch crops is recommended to mitigate climate changes. This study aimed to determine the influence of water deficit on phosphorus (P) content and accumulation in the above-ground biomass of spring barley and Italian rye-grass growing separately and in the mixture, and on the inter-species interactions between these crops. The study was based on a pot experiment established in accordance with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Various species provide complimentary use of environmental resources in a mixture in contrast to pure stands. The recent findings confirmed the benefits of intercropping, such as increased nitrogen uptake by cereals cultivated in a mixture with legumes [1][2][3], and more efficient use of water and nutrients in soil profile [4]. Different species in the mixtures also use field space more effectively [5], i.e., in weather conditions unfavorable for the growth of one species, the companion crop usually grows better [6,7].…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Various species provide complimentary use of environmental resources in a mixture in contrast to pure stands. The recent findings confirmed the benefits of intercropping, such as increased nitrogen uptake by cereals cultivated in a mixture with legumes [1][2][3], and more efficient use of water and nutrients in soil profile [4]. Different species in the mixtures also use field space more effectively [5], i.e., in weather conditions unfavorable for the growth of one species, the companion crop usually grows better [6,7].…”
supporting
confidence: 60%
“…The water content in the soil is a factor that intensifies the inter-species competition, as was shown for barley, undersown with rye-grass, which further weakens the phosphorus uptake by both barley and rye-grass [4]. Water deficit in the soil resulted in barley being a stronger competitor, with rye-grass for phosphorus.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Treder et al [62] showed that barley had a stronger negative effect on wheat than vice versa, as shown in smaller increases in the dry weight of plants from tillering to heading. The competitive advantage of barley results from, inter alia, its uptake of nutrients such as nitrogen [63] or phosphorus [64], which is better and more efficient than that of co-occurring plants. Tosti et al [65] confirmed the aggressiveness and dominance of barley including in mixture with legumes, especially under conditions of high nitrogen content in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research suggests that, even if water deficit intensifies competition between plants, this is manifested in the nutrient uptake/accumulation in biomass (mostly linked to biomass volume). Its content tends to be unaffected by the interaction of these stress factors [71].…”
Section: Nutrients In Post-harvest Residuesmentioning
confidence: 99%